Effects of Different Vegetation Restoration Types on Permeability and Water Holding Capacity of Degraded Granite Red Soil - Yonghui Bai; Xuan Zha; Weicheng Wu; Lanhua Mao (Shuitu baochi tongbao, 2023)
[Objective] The effects of different vegetation restoration types on the permeability and water holding capacity of degraded granite red soil were studied in order to provide a theoretical basis for soil and water conservation and accurate restoration of degraded red soil in this area. [Methods] With seriously degraded granite red soil and natural forest (NV) as the control treatment, we determined the soil permeability and soil water holding capacity of degraded granite red soil under different vegetation restoration types using field investigation, laboratory analysis, and the ring knife method. [Results] Soil permeability decreased with increasing soil depth for different vegetation restoration types. The characteristic values of soil infiltration followed the order of initial infiltration rate > average infiltration rate > stable infiltration rate. The soil permeability and the total amount of soil permeability in the first 30 min for the different vegetation types were compared with that of NV. Soil permeability and total soil permeability in the first 30 min followed the order of NV > arbor, shrub, grass (ASG) > grass in irrigation ditches (GGH) > closed canopy (CC) > low-efficiency forest transformation (IFT) > grass sown in the whole slope (FSG) > severely degraded land (HDL). The sequence of saturated water storage in the 0—40 cm soil layer followed the order of NV > ASG > GGH > CC > IFT > FSG > HDL. Redundancy analysis of soil permeability indexes and soil physical and chemical properties from the 0—5 cm soil layer showed that soil hardness, soil bulk density, silt content, and sand content were the factors that restricted soil permeability, and soil organic carbon, total nitrogen, total phosphorus, available phosphorus, total potassium, available potassium, pH value, and clay content were the important factors that could increase soil permeability. [Conclusion] ASG was the best vegetation restoration type to increase soil permeability and water holding capacity.